2015
DOI: 10.1074/jbc.m114.627554
|View full text |Cite
|
Sign up to set email alerts
|

Potential Prepore Trimer Formation by the Bacillus thuringiensis Mosquito-specific Toxin

Abstract: Background: The molecular description of oligomeric pore formation by B. thuringiensis insecticidal toxins remains unclear.Results: Cry4Ba mosquito-active toxins assemble into a stable prepore trimer upon interaction with non-ionic micelles or lipid membranes. Conclusion: A membrane-bound state of monomers is required for facilitating a potential trimer assembly. Significance: This study reveals a requirement of membrane-bound monomers for forming a prepore trimer capable of perturbing target membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 46 publications
(63 reference statements)
2
17
0
Order By: Relevance
“…This similar finding could be observed in some other bacterial protein toxins from entirely different family, for instance, Bacillus thuringiensis Cry4Ba insecticidal protein, which was also demonstrated to form a trimeric pore structure [36,37]. These two pore-forming toxins potentially share a similar pore structure and mechanism of pore formation, although they have no sequence similarities outside of their pore-lining constituents.…”
Section: Resultssupporting
confidence: 75%
“…This similar finding could be observed in some other bacterial protein toxins from entirely different family, for instance, Bacillus thuringiensis Cry4Ba insecticidal protein, which was also demonstrated to form a trimeric pore structure [36,37]. These two pore-forming toxins potentially share a similar pore structure and mechanism of pore formation, although they have no sequence similarities outside of their pore-lining constituents.…”
Section: Resultssupporting
confidence: 75%
“…In Vibrio cholerae cytolysin, variants that could not form oligomers lost the vast majority of their haemolytic activities against human erythrocytes (Rai & Chattopadhyay, 2015). It was also shown that some Cry toxins, such as Cry1A, Cry3, Cry4, and Cry11, could form oligomeric structures when activated in the presence of midgut receptors or brush border membrane vesicles (Gómez et al, 2014;Munoz-Garay et al, 2009;Rausell et al, 2004;Sriwimol et al, 2015). Here, we showed for the first time that the exposure of helices α4 and α5 could trigger the oligomerisation of Cry2Ab, resulting in the formation of a 250-kDa oligomeric structure (Figure 5a).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Cry1AbMod inserted in synthetic membranes showed a trimeric organization in 2D crystals observed by electron microscopy 29 . Similarly the Cry4Ba toxin showed a trimeric organization after incorporation into synthetic membrane observed by electron microscopy 28 . The trimeric 3D structure of Cry4Ba was used to construct a model of the trimeric structure of Cry4Aa and the authors hypothesized that this structure may resemble the oligomer structure involved in pore formation and toxicity of Cry4Aa 30 .…”
Section: Introductionmentioning
confidence: 89%
“…It was shown that similar to the Cry1A toxins, the Cry11Aa and Cry3Aa toxins also require binding to CAD to oligomerize 25 27 . In contrast the Cry4Ba toxin is an exception because it is able to oligomerize in vitro in the absence of CAD binding 27 , 28 .…”
Section: Introductionmentioning
confidence: 99%